Pengaruh Gaya Pukul Terhadap Intensitas Bunyi Pada Alat Musik Ketipung - Prihandono, Trapsilo; Handayani, Rif'ati Dina; Miftahul, Miftahul; Anggraeni, Firdha Kusuma Ayu (Universitas Jember, 2023)
This study aims to determine the effect of striking force on the sound intensity of the ketipung musical instrument made of paralon pipes with a length of 20 cm and a diameter of 114 mm on the resulting sound intensity. The research data was obtained using the experimental method. Different styles indicate different sound intensity levels, the higher the force applied, the higher the resulting sound intensity and vice versa, the lower the potential energy, the lower the sound intensity, following the equation y = 3.5341e0.7416x with y as a level function Sound intensity and x as the hitting force. Based on the results of the analysis, it can be concluded that the relationship between the hitting force per unit area and the sound intensity follows an exponential equation.